Investigation of Double Screw Compressor Characteristic based on Experimental in Industry - Aulia, Nur Fatowil; Surindra, Mochamad Denny; Su”™udy, Ahmad Hamim; Apriandi, Nanang; Ulum, Muhammad Showi Nailul; Priyoatmojo, Slamet (Eksergi, 2023)
Large-scale compressed air equipment is the only way to meet the demand for air for production facilities such as the pharmaceutical, automotive, or combustion processes industries. As one of the main driving components in the air compressor system, the double screw determines the reliability and performance of the entire compressed air system. Double screw compressors are a promising option for use in large-scale compressed air systems due to their high efficiency and reliability. The double screw profile has been specially designed to increase compression capability over a period of more than 24 hours with a range of 400 to 385 m3 per hour. The cooling oil works well keeping the compressor temperature constant at around 100 0C, even though there are very active temperature fluctuations. On the working pressure side the compressor as a whole is constant, although there is a significant spike in the dryer pressure. The dryer pressure experienced a significant increase reaching 6.9 Bar in the sixth data collection, while the cooling oil pressure and tank pressure were the same at 6.6 Bar, and the air pressure was 6.3 Bar. The results of observing the performance of compressors during industrial operation have presented the ideal working conditions for double screw compressors reaching 58.4 kJ/kg, while the actual working conditions of compressors are 66.6 kJ/kg. Overall, the average compressor efficiency is 87.81%.